Intercropping grapevine with Solanum nigrum enhances their cadmium tolerance through changing rhizosphere soil microbial diversity - Pu, Changbing; Huang, Ziyao; Jiang, Xuefeng; Zhu, Jiawei; Lin, Lijin; Zhang, Xiaoli; Xia, Hui; Liang, Dong; Wang, Jin; Lv, Xiulan (Frontiers in Microbiology, 2025)
IntroductionCadmium (Cd), a toxic heavy metal, has increasingly impacted vineyard soils and grapevine (Vitis vinifera) production in recent years. Intercropping with the hyperaccumulator plant Solanum nigrum has emerged as a promising strategy to improve soil health and increase plant resilience to the Cd-contaminated soil.MethodsThis study investigated the effects of intercropping grapevine with S. nigrum (IntVVSN) on the soil enzyme activity and microbial community.ResultsCompared with the monocultures of S. nigrum and grapevine, IntVVSN increased the activities of soil sucrase, soil urease, and soil cellulase, and decreased the activities of soil amylase, and soil neutral phosphatase. The microbial community in IntVVSN showed higher abundances of beneficial groups such as Acidobacteriota, Actinobacteriota, and Chloroflexi. These groups were involved in the metal detoxification and nutrient cycling, indicating their potential role in enhancing Cd tolerance. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis revealed the distinct metabolic adaptations in IntVVSN under Cd-contaminated soil, with significant upregulation of pathways related to the secondary metabolite synthesis, carbohydrate metabolism, glycan biosynthesis, nucleotide metabolism, and protein processing. The changes in microbial composition, along with the enhanced nutrient cycling indicated by increased soil enzyme activities, suggest a healthier and more resilient soil environment. This, in turn, contributes to improved Cd tolerance in grapevines.ConclusionThis study highlights the phytoremediation potential of S. nigrum intercropping, which promotes sustainable agricultural practices in Cd-contaminated soil by improving plant growth and resilience to heavy metal stress.